Herbaceous plant diversity mediates saline-alkaline soil improvement in the yellow river delta - Wang, Xiao; Lu, Zhaohua; Yan, Jingyao; Wang, Ge; Chen, Xiaohui; Xia, Jiangbao (Frontiers in Microbiology, 2025)
ObjectivesSoil salinization is a primary constraint on plant colonization and ecosystem stability in the Yellow River Delta. However, there is currently a significant lack of research concerning the improvement of saline-alkaline soil quality in the Yellow River Delta, particularly regarding the enhancement of plant communities in saline-alkaline soil. Therefore, undertaking saline-alkaline soil remediation is particularly crucial for enhancing the ecological adaptability of plant communities.MethodsShandong Yellow River Island National Wetland Park, a representative habitat within the Yellow River Delta, were selected as the study area. Moreover, a comprehensive survey of herbaceous plant communities was performed, and the community types, α and β diversity, soil physicochemical properties indicators were determined and analyzed. The effects of different herbaceous plant communities on soil physicochemical properties were investigated. Principal component analysis (PCA) and fuzzy membership functions were used to comprehensively evaluate the improvement effect of different herbaceous plant communities on saline–alkaline soil quality. The study critically evaluated the efficacy of different herbaceous plant communities in improving saline–alkaline soils within the study area.Results(1) The study area contained four main formation groups and ten formations. Our findings revealed pronounced functional disparities among the communities: the Artemisia scoparia and Aeluropus sinensis communities demonstrated high diversity and stability, whereas the Suaeda salsa community exhibited low diversity and poor viability. (2) The herbaceous plant community significantly affected the physicochemical properties of the 0–20 cm soil layer. Although soil bulk density (BD) and pH remained unaffected, communities with higher diversity, particularly A. scoparia and S. salsa, most effectively reduced soil salinity by regulating ions (Na+, Cl–, SO42–). Furthermore, specific communities differentially increased soil nutrientsaS. salsa, A. scoparia, and Phragmites australis communities were important for increasing soil total nitrogen (TN), available phosphorus (AP), and soil organic matter (SOM), respectively. However the proliferation of plant communities exerts a pronounced inhibitory effect on soil available potassium (AK). (3) Principal component analysis (PCA) and composite factor scores ultimately revealed that the S. salsa, A. scoparia, and P. australis communities were the most effective communities for comprehensive soil quality improvement on Yellow River Island.ConclusionIn summary, it is evident that herbaceous plant communities with high diversity yield the most effective soil salinity reduction and improvement outcomes on Yellow River Island. Coastal saline-alkaline soils exhibit elevated levels of readily available potassium due to external inputs; consequently, the capacity of herbaceous plant communities to reduce AK serves as a crucial criterion for evaluating their soil amelioration efficacy. Furthermore, given the spatial heterogeneity of soil salinity on the Yellow River Island, the configuration of soil-improving plant communities must balance ecological and cost-effectiveness considerations.